PS-050 Subvisible particulate matter in intravenous preparations - a comparison of innovator and generic diclofenac sodium. (24th March 2015) - Lehner, E; Haider, D
Abstract : Background: Hazardous effects are brought about by sub-visible particulate contaminants of intravenous preparations being administered into the bloodstream. Pathological consequences ultimately leading to severe harm may result. Purpose: To compare often-used drugs in their innovator and generic form and to optimise the workflow in busy work environments to improve patient safety. Mixtures of 0.9% sodium chloride solution and two diclofenac sodium preparations (Voltaren and Diclobene) and the effect of a buffer were investigated regarding their particulate count and size. Material and methods: 250 millilitres (mL) of sodium chloride 0.9% solution was mixed with either Diclobene 75 milligram (mg) or Voltaren 75 mg/3 mL injectable solution and the required buffer containing sodium bicarbonate solution. The number of particles greater than or equal 10 micrometres (µm) and 25 µm were counted shortly after mixing the components and after 30, 60, 90, 120 and 150 min. Results: The prepared Diclobenesolution had a consistently low particulate count which was way below the threshold value for sub-visible particulate matter contamination regulated by the European Pharmacopoeia whereas Voltaren bicarbonate solutions had a high and fluctuating number of particles exceeding the threshold value. Surprisingly the mixture of Voltaren without the required buffer had an average particulate count below the compulsory threshold. Conclusion: The measurements conducted resulted in substantial changes of neither particulate count nor size in the Diclobeneand the Voltaren preparations. Mixtures of Diclobene with sodium chloride 0.9% solution resulted in a considerably lower particulate count than the Voltaren mixture. Taken into account that adding the buffer to the preparation of Voltaren is an additional step, Diclobene might be a better choice in a busy ward environment thus enhancing patient safety. References: Jack T, Brent BE, Boehne M, et al . Analysis of particulate contaminations of infusion solutions in a pediatric intensive care unit. Intensive Care Med 2010;36(4):707–11 Walpot H, Franke RP, Burchard WG, et al . Particulate contamination of infusion solutions and drug additives within the scope of long-term intensive therapy. Anaesthesist 1989;38(10):544–8 No conflict of interest.